Effect of load sequence interaction on bond-wire lifetime due to power cycling - Zoubir Khatir; Son-Ha Tran; Ali Ibrahim; Richard Lallemand; Nicolas Degrenne (Scientific Reports, 2021)
Abstract Experimental investigations on the effects of load sequence on degradations of bond-wire contacts of Insulated Gate Bipolar Transistors power modules are reported in this paper. Both the junction temperature swing ( $$Δ T_{j}$$ Δ T j ) and the heating duration ( $$t_{ON}$$ t ON ) are investigated. First, power cycling tests with single conditions (in $$Δ T_{j}$$ Δ T j and $$t_{ON}$$ t ON ), are performed in order to serve as test references. Then, combined power cycling tests with two-level stress conditions have been done sequentially. These tests are carried-out in the two sequences: low stress/high stress (LH) and high stress/low stress (HL) for both $$Δ T_{j}$$ Δ T j and $$t_{ON}$$ t ON . The tests conducted show that a sequencing in $$Δ T_{j}$$ Δ T j regardless of the direction “high-low” or “low–high” leads to an acceleration of degradations and so, to shorter lifetimes. This is more pronounced when the difference between the stress levels is large. With regard to the heating duration ( $$t_{ON}$$ t ON ), the effect seems insignificant. However, it is necessary to confirm the effect of this last parameter by additional tests.